Molecular Pathways: Niches in Metastatic Dormancy - Yumoto, Kenji (2014)
Despite the best available treatments for primary tumors, cancer can return, even after a long disease-free interval. During this period, cancer cells are believed to lie dormant in either primary, metastatic sites, or independent sites like bone marrow, effectively escaping adjuvant cytotoxic treatments. To date, little is known about how these cells transition to dormancy, or how they are reactivated if cancer recurs. Recent studies have revealed the effects of tumor microenvironment, or niche, on the regulation of tumor dormancy via the signaling pathways of growth arrest-specific 6 (GAS6), bone morphogenetic protein 7 (BMP7), and transforming growth factor beta-1 (TGF-β1), and that the balance between activation of p38 mitogen-activated protein kinase (MAPK) and extracellular signal-regulated kinase (ERK) MAPK plays a pivotal role in tumor dormancy. In this review, we will discuss tumor dormancy from the perspective of the niche, and consider potential therapeutic targets. Greater understanding of the mechanisms involved will help guide innovation in the care of advanced cancer patients.